STRATEGI PENGEMBANGAN OBJEK WISATA SAJUTA JANJANG NAGARI PAKAN SINAYAN KECAMATAN BANUHAMPU KABUPATEN AGAM PROVINSI SUMATRA BARAT - Insani, Taufan Ikhlas; Iskarni, Paus (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study examines the tourist attraction field in Sajuta Janjang and aims to identify the factors that drive and inhibit tourist attraction development in the area. The research follows a quantitative approach using SWOT analysis and TAPAK analysis methods. The research was conducted in the Kenagarian Pakan Sinayan Kecamanatan Banuhampu Agam Regency of West Sumatra Province, focusing on the Sajuta Janjang tourist area. The findings reveal that Sajuta Janjang has the potential to become a prominent tourism destination in Agam Regency, thanks to its beautiful, cool, and pristine natural panorama and the comfortable atmosphere it provides for visitors. However, there are some inhibiting factors that need to be addressed, including inadequate cleanliness, insufficient promotion, and the rise of competing attractions. Based on these findings, it is important to strategically plan and develop Sajuta Janjang to maximize its potential as a flagship tourist attraction in the region